Search for the Genuine Khayyam (Texas Journal of Multidisciplinary Studies, 2022)
This article paid particular attention to the discovery of Hayam in England through the translation of Fitgerald. His translation have been approved by most readers. The reason for the success of E. Fitzgerald in the English exposition of Rubai Hayam is that he relied on the principles of free translation